Defining physical differences between U16 national team and non- national team basketball players - Lampinen, R. (2011)
The purpose of the research is to determine does physical test separate U16 national team players from non-national team players. When the research started, there was assumed that U16 national team players have better results in physical tests than non-national team players. The material of this thesis is constructed from broader research. This broader research is funded by Ministry of Education and it includes test results of football, basketball, and ice hockey. The research included sport specific technical tests, anthropometrical tests, physical tests, and questionnaires related to players training background, self- evaluation and coach assessment. Only the results of physical tests in basketball are analyzed in this thesis. The thesis includes a journey from physical analysis of basketball players, human growth and development to specialization models. The thesis presents what factors has an affect on human performance and how the development towards the life of an ath-lete happens. The teams were tested in their own operating environment, during August and Octo-ber 2010. U16 national team players were tested with their own club teams. Investigated subjects (N= 115) constituted of 1995 born male basketball players. The U16 national team players (N1) consisted of 23 players and non-national team players (N2) consisted of 92 players. All the players belonged to B-junior level. There were 12 teams and U16 national team that were tested and Finnish Basketball Association choose the teams for this research. The hypothesis of this research is following: The U16 national team players have better results in physical abilities tests than non-U16 national team players. Mean results of the U-16 national team are better, but there is not statistically significant difference between the groups in all tested areas. Statistically there is significant difference in 20m speed test (P<0.01), and counter movement jump (P<0.01).